Empowering rural women through gender and nutrition education amid the COVID-19 crisis: Evidence from Myanmar's Central Dry Zone - Ragasa, Catherine; Lambrecht, Isabel B.; Mahrt, Kristi; Aung, Zin Wai (Elsevier, 2023)
The COVID-19 pandemic had negative impacts on nutrition and strained intrahousehold relations, particularly among poorer households. Social protection programs intended to mitigate these impacts mainly operated through handing out cash or in-kind items to vulnerable households. Yet social and behavior change communication (SBCC) intervention on gender and nutrition could be another option. We assess the impact of a nutrition and gender SBCC intervention implemented as a cluster-randomized controlled trial in 30 villages in Myanmar's Central Dry Zone during the first year of the COVID-19 pandemic. We rely on data from a baseline survey implemented in February 2020 and a phone survey implemented in February–March 2021. Two indicators of women's empowerment―input in productive decisions and access to and input in decisions over credit―improved, indicating that SBCC interventions can contribute to changing gendered perceptions and behaviors. Some empowerment indicators did not change, indicating it may take more time to change deeply ingrained gender norms—including tolerance toward intimate partner violence. In treatment villages, women's dietary diversity scores were higher by half a food group out of 10. More women in treatment villages consumed nuts, milk, meat or fish, and vitamin A–rich foods daily than in control villages.